Easternmost Locality Record and Morphological Data of Cyrtopodion scabrum (Heyden, 1827) (Squamata: Gekkonidae) in southeastern Anatolia, Turkey - Halime Koç; Ufuk Bülbül; Zeynep Aslan (Turkish Journal of Bioscience and Collections)
The locality record of the Rough Bent-toed Gecko (Cyrtopodion scabrum) from the Silopi District of the Şırnak Province of Turkey was provided in the present study. The new locality record extended the distribution area of the species 40 km to the east. Data based on meristic pholidosis characters, metric measurements and color-patter features of the specimens from Silopi were given in detail and compared with data given in the previous literature.